Hypermentalizing and the Problem of the Opacity of Mental States - Haroyan, Nelli; Melikyan, Mari (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
Mentalization, the ability to understand and interpret one’s own and others’ behavior in terms of underlying mental states, is a fundamental concept in contemporary clinical psychology. This work conceptualizes hypermentalizing not as an excess of mature mentalization, but as a manifestation of an infantile psychic organization. It is proposed that hypomentalizing and hypermentalizing are not opposite poles, but two different expressions of the same structural failure: the inability to tolerate the opacity of another person’s mental reality. The theoretical analysis integrates perspectives from mentalization theory, psychoanalysis, and phenomenological psychopathology. It is argued that hypermentalizing is structurally linked to prementalizing modes, magical and paranoid thinking, and intolerance of uncertainty. The work further emphasizes that the defining feature of mature mentalization is not greater certainty about another person’s mind, but the capacity to maintain a “not-knowing stance” and tolerate the partial unknowability of the other’s inner world. Consequently, hypermentalizing is defined as a rigid and partially reality-disconnected form of mentalization characterized by pseudo-certainty and reflecting features of an early, infantile organization of the psyche.
Keywords: hypermentalizing; mentalization; psychological infantilism; pretend mode; opacity of minds; reflective function; magical thinking; paranoid thinking